2012
DOI: 10.1007/s00210-012-0727-1
|View full text |Cite
|
Sign up to set email alerts
|

Tetracyclines and pain

Abstract: Tetracyclines are natural or semi-synthetic bacteriostatic agents which have been used since late 1940s against a wide range of gram-positive and gram-negative bacteria and atypical organisms such as chlamydia, mycoplasmas, rickettsia, and protozoan parasites. After the discovery of the first tetracyclines, a second generation of compounds was sought in order to improve water solubility for parenteral administration or to enhance bioavailability after oral administration. This approach resulted in the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 137 publications
(192 reference statements)
0
21
0
Order By: Relevance
“…Therefore, we hypothesize that all these semi-synthetic tetracycline derivatives share similar anti-inflammatory activities that may underlie suppression of experimental pain. Among them, minocycline is the most widely studied [4]. It has been shown that minocycline, directly or indirectly, prevents activation of many enzymes involved in the synthesis of multiple inflammatory mediators in macrophage/microglia or neuronal cell lines or in cell-free assays.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, we hypothesize that all these semi-synthetic tetracycline derivatives share similar anti-inflammatory activities that may underlie suppression of experimental pain. Among them, minocycline is the most widely studied [4]. It has been shown that minocycline, directly or indirectly, prevents activation of many enzymes involved in the synthesis of multiple inflammatory mediators in macrophage/microglia or neuronal cell lines or in cell-free assays.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that minocycline, directly or indirectly, prevents activation of many enzymes involved in the synthesis of multiple inflammatory mediators in macrophage/microglia or neuronal cell lines or in cell-free assays. Among them, phospholipase A 2 , different protein kinase C isoforms, multiple mitogen-activated protein kinases, phosphatidylinositol 3-kinase/Akt, inducible nitric oxide synthase, cyclooxygenase (COX)-2, microsomal prostaglandin E synthase-1, 5-lipoxygenase and poly(ADP-ribose) polymerase-1 [4]. Besides anti-inflammatory actions on macrophages, microglia and neurons, direct actions on excitability of primary afferent neurons may also explain minocycline’s suppressive effects on experimental pain [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations